Mapping and Application of Roof Joint Patterns for Ground Control inAn Illinois Mine - Kenny D. Basnett (International Conference on Ground Control in Mining, 2011)
An analysis of the Roof Falls Data Base (RFDB) for underground coal mines in Illinois for the period 2004?2008 indicated that about 80% of the roof falls occur at intersections and are associated with geologic anomalies or a rapidly changing geologic environment. Most falls are associated with anomalies such as clay dikes, differential compaction faults, shear zones, joints and fractures, and geologic structure. Therefore, a better analysis of the geology with emphasis on mapping anomalies such as joints and fractures and their application is necessary to improve ground conditions and safety. Such studies within Illinois Coal Basin are limited. This paper presents a mapping study of the joint orientations with documentation of dip of the several lithological units that lie directly above the Herrin No. 6 Coal seam around southern Illinois. These units include the Energy Shale, Anna Shale, and Brereton Limestone. The mapping was done in three mines and the data were plotted on a stereographic projection to determine the average characteristics of joint planes. The study mines included two deep underground mines and one shallow highwall mine. This study has helped identify favorable mining and support orientations in areas of highly variable geology. These are currently under review by the cooperating coal company for experimental roof control studies.